Numerical study on the flexural behaviour of slim-floor beams with hollow core slabs at elevated temperature. (1st February 2019) - Albero, V.; Espinós, A.; Serra, E.; Romero, M.L.; Hospitaler, A.
Highlights: A model for the slim-floor beam behaviour at elevated temperatures is presented. The presented model is validated against experimental data. A parametric study is carried out to provide extended results. Detailed design recommendations are provided to assist practitioners. Abstract: Slim-floor beams are a novel typology of steel beams where the steel profile is fully embedded within the concrete floor depth. While the use of this system is increasing fast in the construction practice, the available investigations on its fire performance are still scarce. This paper focuses on analysing the fire behaviour of slim-floor beams combined with hollow core slabs as flooring system. Two configurations are studied, namely Integrated Floor Beam (IFB) and Shallow Floor Beam (SFB). A finite element model is developed and validated by comparison with experimental results available in the literature as well as with thermal tests carried out by the authors. Subsequently, parametric studies are conducted with the aim of providing practical design recommendations. The influence of the composite beam configuration, concrete type, longitudinal reinforcement and steel plate thickness is studied. The conclusions drawn in this paper suggest that the SFB configuration may provide a significant enhancement in terms of fire resistance compared to IFB, provided that the appropriate combination of the parameters studied is used.